Reflection about the hemodialysis water microbiological quality in Brazil - Gabriela Corrêa Carvalho; Kamal Dua; Gaurav Gupta; Adriana Bugno; Terezinha de Jesus Andreoli Pinto (Universidade de São Paulo, 2022)
Abstract Dialysis has been widely used in the treatment of patients with chronic kidney diseases and is considered a global public health issue. This treatment, which has changed the prognosis and quality of life in patients with chronic renal failure, can lead to complications that are often fatal. For this reason, there is a need for validation of alternative tests that favor the monitoring of treated water for dialysis in real-time to promote and prevent injuries to patients submitted to this procedure.